Peripheral Immune Activation in Mice Elicits Unfolded Protein Responses Independent on MyD88 Pathway in the Liver but not the Hypothalamus and Hippocampus - Yamawaki, Yosuke; Kimura, Hitomi; Nagata, Susumu; Ozawa, Koichiro; Hosoi, Toru (Frontiers in Physiology, 2022)
Neuroimmune interactions between the immune system and CNS as well as peripheral organs such as the liver play a key role in the pathophysiological state of diseases. Unfolded protein responses (UPRs), which are activated by cells in response to endoplasmic reticulum stress, have been linked to the occurrence of inflammation diseases, neurodegenerative diseases, and metabolic disorders such as type 2 diabetes. Peripheral injection of lipopolysaccharide (LPS) is known to induce a systemic inflammatory response, along with fever, anorexia, and depressive behaviors. LPS also elicits UPRs, although the underlying physiological mechanism remains unclear. In the present study, we investigated whether peripheral activation of the immune system can elicit UPRs in the CNS and liver. Peripheral injection of LPS is known to elevate pro-inflammatory cytokines in the liver and hypothalamus. We report that LPS-induced systemic inflammation elicits UPRs in the liver, but not the hypothalamus. Injection of LPS upregulated the expression levels of glucose-regulated protein 78 and pro-apoptotic transcription factor C/EBP homologous protein, along with increased splicing of X-box binding protein 1 mRNA in the liver, but not in the hypothalamus. Myeloid differentiation primary response 88 (MyD88), an adaptor protein, is known to play a key role in the signal transduction of LPS mediated by Toll-like receptor 4. Using MyD88 deficient mice, we found that LPS-induced UPRs occurred independently of MyD88 expression. In summary, peripheral activation of the immune system elicits UPRs in the liver, but not the hypothalamus, which may have implications for the pathophysiology of diseases.